2019
DOI: 10.1101/523001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Effector Response of Amnion- and Adipose-Derived Mesenchymal Stem Cells to Inflammation; Implications for Intradiscal Therapy

Abstract: 1Intervertebral disc degeneration (IVDD) is a progressive condition marked by 2 inflammation and tissue destruction. The effector functions of mesenchymal stem cells (MSCs) 3 make them an attractive therapy for patients with IVDD. While several sources of MSCs exist, the 4 optimal choice for use in the inflamed IVD remains a significant question. Adipose (AD)-and 5 amnion (AM)-derived MSCs have several advantages compared to other sources, however, no 6 study has directly compared the impact of IVDD inflammati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Our data showing that conditioned medium from IL‐1β‐treated chondrocytes after complete removal of EVs and wash out of IL‐1β was still able to reduce the chondrogenic differentiation of C3H10T1/2 cells even though to a lesser degree than EV‐containing medium suggest that articular chondrocytes in an inflammatory state release a variety of factors and cytokines, including but not limited to IL‐6, IL‐8, tumor necrosis factor‐α, and MMPs and EVs that inhibit chondrogenic differentiation. Our findings are consistent with the previous findings showing reduced chondrogenic differentiation of MSCs in the presence of inflammatory cytokines …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our data showing that conditioned medium from IL‐1β‐treated chondrocytes after complete removal of EVs and wash out of IL‐1β was still able to reduce the chondrogenic differentiation of C3H10T1/2 cells even though to a lesser degree than EV‐containing medium suggest that articular chondrocytes in an inflammatory state release a variety of factors and cytokines, including but not limited to IL‐6, IL‐8, tumor necrosis factor‐α, and MMPs and EVs that inhibit chondrogenic differentiation. Our findings are consistent with the previous findings showing reduced chondrogenic differentiation of MSCs in the presence of inflammatory cytokines …”
Section: Discussionsupporting
confidence: 94%
“…Our findings are consistent with the previous findings showing reduced chondrogenic differentiation of MSCs in the presence of inflammatory cytokines. 25,26 JOURNAL OF ORTHOPAEDIC RESEARCH ® APRIL 2020…”
mentioning
confidence: 99%
“…In addition, MSCs intravenously injected into the lung microenvironment may also induce an inflammatory response by increasing TNF-α and IL-1β 53 . The acidic environment induced the production of proinflammatory cytokines, such as IL-1β and prostaglandin E2 (PGE 2 ), in ADSCs 54 . PGE 2 has a negative impact on IVD cell health and ECM homeostasis even after short-term exposure 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The degenerative changes in the IVDs, such as the composition of extracellular matrix (ECM), loss of disc cells, proteoglycans and water content, have been suggested to be the consequence of an upregulation of catabolic matrix metalloproteinases (MMPs) and pro-inflammatory (IL-1β, TNF-α, IL-6) gene transcriptions [22][23][24][25][26]. Consistent with the previous reports, we found that mRNA expressions of catabolic (MMP-9, MMP-13) genes were up-regulated in the impact injury groups, especially at day 14 in the low-impact group.…”
Section: Discussionmentioning
confidence: 99%